Chains of fire - Dodd, Christina (Dodd, Christina. Chosen ones., 2010)
After they are torn apart by betrayal, Chosen Ones Samuel Faa, a Gypsy lawyer with the power to control minds, and Isabelle Mason, a wealthy heiress with the power to heal, are reunited when they are trapped underground together.